Zwischen Abweichung und Stereotyp - Jesenovec, Barbara (Acta neophilologica, 2014)
The goal of the following contribution is to analyse the image of the grandmother in two modern German-language novels Lady Berta by Annette Hug and Die schärfsten Gerichte der tatarischen Küche by Alina Bronsky. The paper starts with presenting the historical and cultural development of the grandparent concept with special emphasis on the changing of traditional social role of the grandmother. This historical and sociological background functions as a basis for the following literary analyses of the grandmother's image and representation in the two contemporary novels of Hug and Bronsky. The comparison detects, as suggested by the title, that in spite of the deviations of the grandmother figures the traditional and stereotyped image prevails in the expectations of the granddaughters as well as the readers.
Keywords: "Die schärfsten Gerichte der tatarischen Küche"; "Lady Berta"; babica; Bronsky, Alina, 1978-; German-language literature; Hug, Annette, 1970-; literarne študije; literarni liki; nemška književnost